Caracterización biofísica y funcional de una fosfolipasa del veneno bruto de Bothrops atrox (familia: viperidae) “jergón”, Loreto-Perú - Perez Padilla, Greyci Tatiana (2025)
Snakebite accidents represent a serious public health problem in the Amazon region, with Bothrops atrox being the main cause of most cases. The lack of detailed studies on the isoforms of PLA2 in Bothrops atrox highlights the need for specific investigations to better understand their role in venom toxicity and their potential for therapeutic applications. In this study, we isolated and characterized a PLA2 isoform from the crude venom of Bothrops atrox. The crude venom was purified through two purification stages, and the enzymatic activity of PLA2 was determined. Advanced biophysical characterization techniques, such as mass spectrometry, dynamic light scattering (DLS), SEC MALS, and circular dichroism (CD), were used to determine the molecular mass, size, oligomeric state, purity, thermal stability, and secondary structure of the enzyme. Additionally, protein crystallization experiments were performed. An acidic PLA2 isoform was isolated and purified with a yield of 5% from the crude venom, showing high catalytic activity, with an optimal concentration of 6.25 µg for the degradation of lipoproteins. Biophysical characterization indicated that PLA2 has a dimeric oligomeric state and is highly thermostable, with a transition temperature of 58°C. Crystallization attempts resulted in low-resolution crystals, preventing the determination of a detailed crystallographic model. This study establishes a solid foundation for subsequent investigations into the development of antivenoms and future understanding of the functional and structural diversity of PLA2s from Bothrops atrox.